Jimmy Smith perspective on investing in resilience for food and nutrition security - Smith, Jimmy W. (International Food Policy Research Institute, 2014)
Perspectives by Jimmy Smith, Director General, International Livestock Research Institute (ILRI), Kenya, at the IFPRI 2020 conference, "Building Resilience for Food and Nutrition Security" May 15-17, 2014, Addis Ababa, Ethiopia. More information at http://www.2020resilience.ifpri.info